Precise 3D Localization of Intracerebral Implants Using a Simple Brain Clearing Method - Julien Catanese; Tatsuya C. Murakami; Adam Catto; Paul J. Kenny; Ines Ibañez-Tallon (Journal of Integrative Neuroscience, 2024)
Background: Precise localization of intracerebral implants in rodent brains is required for physiological and behavioral studies, particularly if targeting deep brain nuclei. Traditional histological methods, based on manual estimation through sectioning can introduce errors and complicate data interpretation. Methods: Here, we introduce an alternative method based on recent advances in tissue-clearing techniques and light-sheet fluorescence microscopy. This method uses a simplified recipe of the Clear, Unobstructed Brain/Body Imaging Cocktails and Computational Analysis (CUBIC) method, which is a rapid clearing procedure using an aqueous-based solution compatible with fluorescence and fluorescence markers. We demonstrate the utility of this approach in anesthetized transgenic mice expressing channelrhodopsin-2 (ChR2) and enhanced yellow fluorescent fusion (EYFP) protein under the choline acetyltransferase (ChAT) promoter/enhancer regions (ChAT-ChR2-EYFP mice) with implanted linear silicon optrode probes into the midbrain interpeduncular nucleus (IPN). Results: By applying the red fluorescent DiD' dye (DiIC18(5) solid (1,1′-Dioctadecyl-3,3,3′,3′-Tetramethylindodicarbocyanine, 4-Chlorobenzenesulfonate Salt) to the electrode surface, we precisely visualize the electrode localization in the IPN of ChAT-ChR2-EYFP mice. Three-dimensional brain videos from different orientations highlight the potential of this method. Optogenetic responses recorded from electrodes placed in the IPN validate these findings. Conclusions: This method allows for precise localization of brain implantation sites in transgenic mice expressing cell-specific fluorescence markers. It enables virtual brain slicing in any orientation, making it a useful tool for functional studies in mice.